The Effect of the Fun Learning Method on Fourth-Grade Students’ Reading Comprehension of Short Story Texts - Kholidah, Sri; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This research was motivated by the low learning outcomes in reading comprehension of short stories among fourth-grade students at SD Negeri 114 Pagaran Sigatal. The use of monotonous and conventional teaching methods made students tend to be passive and unenthusiastic during the reading comprehension process. To address this issue, the study aimed to investigate the effect of the Fun Learning method on students’ reading comprehension outcomes. This study was a quasi-experimental research using a control group pre-test post-test design involving 50 students, consisting of 25 students in the experimental class and 25 in the control class. The pre-test results showed that the average score of the experimental class was 69.2, while the control class was 69.72. After the treatment, the post-test average score of the experimental class increased to 80.2, while the control class only reached 75.4. The maximum score in the experimental class increased from 75 to 95, and the minimum score from 55 to 70. In contrast, the maximum score in the control class reached only 85, and the minimum was 68. The hypothesis test using the t-test showed that the t-value = 2.668 was greater than the t-table = 1.677 at the 0.05 significance level, indicating that H₀ was rejected and Hₐ was accepted. This means that there is a significant effect of using the Fun Learning method on improving students’ learning outcomes. Furthermore, this method increased students’ active participation, stimulated enthusiasm, and strengthened collaboration through singing and guessing-game activities. The advantage of this method lies in its ability to create an enjoyable learning atmosphere, motivate students to engage actively, and enhance their ability to comprehend texts more deeply. Therefore, the Fun Learning method is a worthy alternative instructional strategy to improve learning outcomes, particularly in reading comprehension skills at the elementary school level